Self‐gated 3D stack‐of‐spirals UTE pulmonary imaging at 0.55T. Issue 4 (16th November 2021) - Javed, Ahsan; Ramasawmy, Rajiv; O'Brien, Kendall; Mancini, Christine; Su, Pan; Majeed, Waqas; Benkert, Thomas; Bhat, Himanshu; Suffredini, Anthony F.; Malayeri, Ashkan; Campbell‐Washburn, Adrienne E.
Abstract : Purpose: To develop an isotropic high‐resolution stack‐of‐spirals UTE sequence for pulmonary imaging at 0.55 Tesla by leveraging a combination of robust respiratory‐binning, trajectory correction, and concomitant‐field corrections. Methods: A stack‐of‐spirals golden‐angle UTE sequence was used to continuously acquire data for 15.5 minutes. The data was binned to a stable respiratory phase based on superoinferior readout self‐navigator signals. Corrections for trajectory errors and concomitant field artifacts, along with image reconstruction with conjugate gradient SENSE, were performed inline within the Gadgetron framework. Finally, data were retrospectively reconstructed to simulate scan times of 5, 8.5, and 12 minutes. Image quality was assessed using signal‐to‐noise, image sharpness, and qualitative reader scores. The technique was evaluated in healthy volunteers, patients with coronavirus disease 2019 infection, and patients with lung nodules. Results: The technique provided diagnostic quality images with parenchymal lung SNR of 3.18 ± 0.0.60, 4.57 ± 0.87, 5.45 ± 1.02, and 5.89 ± 1.28 for scan times of 5, 8.5, 12, and 15.5 minutes, respectively. The respiratory binning technique resulted in significantly sharper images ( p < 0.001) as measured with relative maximum derivative at the diaphragm. Concomitant field corrections visibly improved sharpness of anatomical structures away from iso‐center. The image quality was maintained with a slight loss in SNR for simulated scan times down to 8.5 minutes. Inline image reconstruction and artifact correction were achieved in <5 minutes. Conclusion: The proposed pulmonary imaging technique combined efficient stack‐of‐spirals imaging with robust respiratory binning, concomitant field correction, and trajectory correction to generate diagnostic quality images with 1.75 mm isotropic resolution in 8.5 minutes on a high‐performance 0.55 Tesla system.